Performance indicators that discriminate winning and losing in elite men`s and women`s Rugby Union - Hughes, A.; Barnes, A.; Churchill, S. M.; Stone, J. A. (International Journal of Performance Analysis in Sport, 2017)
This study aimed to identify performance indicators that discriminate winning and losing in elite men`s and women`s Rugby Union during the latest World Cup competitions. The knockout stages of the men`s 2015 Rugby World Cup (n = 8) and women`s 2014 Rugby World Cup (n = 8) were compared. Findings suggest that in the men`s game, winning teams kicked a greater percentage of possession in the opposition 22-50 m with a view to gaining territory and pressuring the opposition (winners = 16%, losers = 7%). In the women`s game successful teams adopted a more possession-driven attacking approach in this area of the pitch. Successful women`s teams appear more willing to attack with ball in hand following a kick receipt and adopt a more expansive game through attacking with wider carries in the outside channels. The percentage of lineouts won on the opposition ball was found to be an important performance indicator that discriminates winners and losers, regardless of sex (winners = 18%, losers = 11%). Findings suggest successful men`s and women`s teams adopt different tactical approaches to knockout competitions, this knowledge should be used as a basis for coaches to develop tactical approaches and training methods which are sex dependent.